Developmental instability, body mass, and reproduction predict immunological response in short-tailed bats - Mellado, Breno; Carneiro, Lucas de O.; Nogueira, Marcelo R.; Herrera, L. Gerardo M.; Cruz-Neto, Ariovaldo P. [UNESP]; Monteiro, Leandro R. (Oxford Univ Press, 2024)
Developmental instability (DI) is a phenomenon whereby organisms are unable to buffer developmental disturbances, resulting in asymmetric variation of paired traits. Previous research has demonstrated a negative relationship between DI, measured as forearm asymmetry, and survival in the bat Carollia perspicillata. This study aims to test the hypothesis that individuals with higher DI exhibit a lower immune response. We measured a delayed-type hypersensitivity to the antigen phytohemagglutinin (PHA) on 74 males and 65 females of C. perspicillata before and after the breeding season (BS). Linear models were used to predict the immunological response based on body mass (BM), forearm asymmetry, sex, BS, and testicle length. The best-fitting model accounted for 29% of the variation in immune response and included asymmetry, BM, sex, and BS as predictors. The immune response was negatively associated with asymmetry and testicle length in males but positively related to asymmetry in females. Both sexes showed a reduced immune response in the late BS. Additionally, the association between immune response and BM changed direction seasonally, with heavier individuals showing weaker responses early in the BS and stronger responses later. Individual variation in male immunity was predicted by individual attributes, whereas variation in immune response in females was mostly seasonal. Our results support the link between DI, survival, and immune response in short-tailed bats, and suggest that the immunological component measured by the PHA response may be under finer selection in males due to its stronger correlation with individual traits.
Keywords: asymmetry; Carollia; delayed-type hypersensitivity; immunocompetence handicap hypothesis; Phyllostomidae; testicle size